2005
DOI: 10.1002/jsfa.2132
|View full text |Cite
|
Sign up to set email alerts
|

A study on degradation kinetics of ascorbic acid in drumstick (Moringa olifera) leaves during cooking

Abstract: The kinetics of ascorbic acid degradation in drumstick (Moringa olifera) leaves as well as in pure ascorbic acid solutions at the initial concentrations present in drumstick leaves over a temperature range of 50-120 • C (isothermal temperature process) has been studied. The degradation kinetics of ascorbic acid was also evaluated in normal open-pan cooking, pressure-cooking and a newly developed and patented fuelefficient eco cooker (non-isothermal heating process). The ascorbic acid degradation followed first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Cooking is often responsible for the greatest losses of ascorbic acid, and the extent of the loss depends upon variations in the cooking methods and periods (Lee and Kader 2000; Nisha et al. 2004; Bineesh et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Cooking is often responsible for the greatest losses of ascorbic acid, and the extent of the loss depends upon variations in the cooking methods and periods (Lee and Kader 2000; Nisha et al. 2004; Bineesh et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Cooking is o en responsible for the greatest losses of ascorbic acid, and the extent of the loss depends upon variations in the cooking methods and periods (Bineesh et al, 2005). Because the preparation and stabilization of home-cooked products, such as soups and sauces from squash pulp, would involve thermal treatments, the ascorbic acid retention in squash pulp held for 30 min at 95 o C was investigated.…”
Section: Evaluation Of Vitamin C Contentmentioning
confidence: 99%
“…Some studies have been reported on the degradation of vitamin C in thermally processed fruits and vegetables like grapefruit juice (Saguy, Kopelman, & Mizrahi, 1978), orange juice (Johnson, Braddock, & Chen, 1995), lime, lemon, grapefruit and tangerine (Alvarado & Viteri, 1989), cupuaçu nectar (Vieira et al, 2000), tomatoes (Dewanto, Wu, Adom, & Liu, 2002), green asparagus (Esteve, Frígola, Martorell, & Rodrigo, 1999), amla (Nisha, Singhal, & Pandit, 2004), drumstick (Bineesh, Singhal, & Pandit, 2005) and strawberry products (Castro, Teixeira, Salengke, Sastry, & Vicente, 2004). However, few works have been reported on kinetic data for vitamin C degradation in leafy vegetables during thermal processing.…”
Section: Introductionmentioning
confidence: 96%
“…Since there are few research studies on the thermal degradation of vitamin C in leafy vegetables (Bineesh et al, 2005;Negi & Roy, 2000), and none at all for watercress thermosonication blanching, the objective of this work was to determine the degradation kinetics of vitamin C in watercress with a combined method of heat and ultrasound. Thus, the findings will help to optimise the design of watercress blanching conditions.…”
Section: Introductionmentioning
confidence: 99%